Esophageal sarcoidosis presenting as pseudodiverticulum - Ohshimo, S.; Theegarten, D.; Tötsch, M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2008)
Sarcoidosis is a multisystem granulomatous disorder that may involve many organs. However, the involvement of the gastrointestinal tract is very rare. This report describes an unusual case of esophageal sarcoidosis presenting as a pseudodiverticulum and reviews the world literature. Our case is also characterized by unusual progression of the esophageal involvement despite stable disease in other organs involved. Myotomy improved the pharyngoesophageal stenosis with no recurrence to date. Physicians should be aware of this rare manifestation, which should be suspected in any sarcoidosis patient complaining about dysphagia.